Boosting oxygen diffusion by micro-nano bubbles for highly-efficient H2O2 generation on air-calcining graphite felt. (20th January 2023) - Ye, Shanshan; Geng, Jianxin; Zhang, Haichuan; Hu, Jianshuang; Zou, Xiyang; Li, Ji
Highlights: Air-calcining oxidation produced more surface oxygen-containing functional groups. Micro-nano bubbles aeration was used for electrochemical H2 O2 generation. O2 transfer rate of micro-nano bubbles was 5 times of that macro bubbles. MNBs aeration generated 2.3-fold H2 O2 yield compared to conventional aeration. Over 96% of coulombic efficiency for H2 O2 generation was obtained by MNBs. Abstract: Electrochemical H2 O2 generation via oxygen reduction has to face dissolved oxygen transfer limitation in aeration system. To mitigate this problem, we proposed to boost oxygen diffusion by micro-nano bubbles (MNBs) for highly-efficient H2 O2 generation on air-calcining graphite felt (GF600). The oxygen transfer coefficient and rate of MNBs were 0.160 min −1 and 0.382 kg m − 3 h − 1, about 4 times and 5 times greater than those of conventional aeration, respectively. As a result, the GF600 electrode under MNBs aeration could produce 140.4 ± 1.6 mg L − 1 H2 O2 with an ultrahigh coulombic efficiency of 97.8 ± 0.9%, but only 47.9 ± 2.5 mg L − 1 H2 O2 with 65.9 ± 3.7% under conventional aeration. By increasing the potential on the GF600 electrode, the H2 O2 production showed the first rising then descending trend with and the optimized potential of −0.6 V. Besides, during 5 cycles the H2 O2 production of GF600 was stably ranged from 124.8 mg L ‒1 to 145.2 mg L ‒1 with high coulombic efficiency of 94.3%−97.8% under MNBs aeration. Thus, micro-nano bubbles could effectively solve O2 mass transfer limitation, paving a promising way for in-situ synthesis of H2 O2 . Graphical abstract: Image, graphical abstract